Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.7150/ijbs.24347
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol accumulation promotes esophagitis via pyroptosis activation

Abstract: Gastroesophageal reflux impairs the mucosal barrier in the distal esophagus, allowing chronic exposure of the squamous epithelium to multitudinous stimulations and inducing chronic inflammation. Esophagitis is a response to inflammation of the esophageal squamous mucosa. Our study clarified that alcohol accumulation could aggravate the progress of esophagitis by inducing pyroptosis; however, Ac-YVAD-CMK, an inhibitor of caspase-1, could effectively suppress the expression of IL-1β and IL-18 both in vivo and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…448 Ac-YVAD-CMK, an irreversible and selective inhibitor of caspase-1, effectively blocked the cleavage of pro-IL-1β and pro-IL-18 and reduced the inflammatory response and is expected to be used to inhibit the progression of esophagitis. 449 Furthermore, Ac-YVAD-CMK suppressed IFI16- or berberine-induced tumor inhibition in hepatocellular carcinoma 335 , 450 (Fig. 6 ).…”
Section: Therapeutic Implicationsmentioning
confidence: 84%
“…448 Ac-YVAD-CMK, an irreversible and selective inhibitor of caspase-1, effectively blocked the cleavage of pro-IL-1β and pro-IL-18 and reduced the inflammatory response and is expected to be used to inhibit the progression of esophagitis. 449 Furthermore, Ac-YVAD-CMK suppressed IFI16- or berberine-induced tumor inhibition in hepatocellular carcinoma 335 , 450 (Fig. 6 ).…”
Section: Therapeutic Implicationsmentioning
confidence: 84%
“… 30 Additionally, Chen et al 31 showed that NLRP3 could active IL‐1β, which is associated with antineoplastic immune responses and tumor development in head and neck squamous cell carcinoma. Furthermore, Wang et al 32 showed that the accumulation of alcohol in the esophagus could trigger caspase‐1‐mediated pyroptosis and the release of IL‐1β and IL‐18, which may be involved in esophageal cancer. Barrett's esophagus (BE) can also activate caspase‐1‐dependent pyroptosis and cause the release of IL‐1β and IL‐18 to enhance the progression of esophageal cancer.…”
Section: The Role Of Pyroptosis In the Association Between Cancer And The Immune Systemmentioning
confidence: 99%
“…Caspase-1 is considered as a pro-inflammatory mediator in GERD. Under conditions of alcohol-induced esophagitis in cell culture and in vivo, was found caspase-1 activation and DNA fragmentation [14]. Caspase-1 converts inactive pro-IL-1β and pro-IL-18 into active pro-inflammatory cytokines, enhances the inflammatory response, induces pyroptosis an inflammatory cell death after its activation various inflammasomes, thus pyroptosis was involved in the occurrence of esophagitis [15,16].…”
Section: Discussionmentioning
confidence: 98%
“…Caspase-1 converts inactive pro-IL-1β and pro-IL-18 into active pro-inflammatory cytokines, enhances the inflammatory response, induces pyroptosis an inflammatory cell death after its activation various inflammasomes, thus pyroptosis was involved in the occurrence of esophagitis [15,16]. The use of an inhibitor of caspase-1 could suppress the activity of IL-1 and IL-18 in vivo and in vitro reducing the inflammatory response so may considered as future therapeutic target [14]. Similar results in determining the role of caspase-1 were obtained in an animal model of esophagitis induced by the introduction of bile acid salts [17].…”
Section: Discussionmentioning
confidence: 99%